Alternative proteins, evolving attitudes: Comparing consumer attitudes to plant-based and cultured meat in Belgium in two consecutive years. (1st June 2021) - Bryant, Christopher; Sanctorum, Hermes
Abstract: Alternatives to conventional meat are considered an increasingly important tool in the drive to reduce consumption of animal products for environmental, public health and ethical reasons. We present two waves of a cross-sectional survey from a nationally representative sample in Belgium in 2019 (n = 1001) and 2020 (n = 1000). Participants answered questions online about their diets, attitudes towards existing plant-based meat alternatives, and attitudes towards cultured meat (grown from animal cells). We find that the proportion of Belgian consumers who said existing plant-based meat alternatives met their needs increased significantly from 44% in 2019 to 51% in 2020. We also find a significant increase in concern for issues related to animal agriculture, in particular the environment. We found no significant change in attitudes towards cultured meat between the two waves; in both 2019 and 2020, 39.3% of Belgian consumers said they would buy cultured meat. Regression analyses revealed that plant-based alternatives were more appealing to women and those with vegetarian diets, whilst cultured meat was more appealing to men. Overall, just 11.2% of consumers are both unsatisfied with existing meat alternatives and unwilling to buy cultured meat, while 43.2% of respondents were positive towards either plant-based or cultured meat, but not both, highlighting the need for a variety of alternative proteins in the market. Both cultured meat and plant-based meat were more appealing to younger consumers and those in the northern, predominantly Dutch-speaking region of Flanders. We discuss the implications of these findings for researchers and those seeking to strategically displace demand for animal products.